ANALISIS STRUKTUR MODAL DAN NILAI TAMBAH ( ECONOMIC VALUE ADDED ) SUATU STUDI PADA PT BANK MUAMALAT Tbk - Liviawati Liviawati; Gusmarila Eka Putri; Hardi Hardi (Jurnal Akuntansi Kompetif, 2026)
Bank Muamalat was the first Islamic bank established in Indonesia. At the time of its inception, Bank Muamalat performed very well, even becoming the largest bank in Indonesia. Following the global crisis, one of the causes of which was COVID-19, Bank Muamalat's performance declined. To improve Bank Muamalat's performance, the government planned to acquire Bank Muamalat through Bank BTN. However, the planned acquisition of Bank Muamalat by Bank BTN was not implemented because, according to news obtained by the author from kompas.com in September 2024, Bank BTN switched to Bank Victory Syariah for acquisition. As a result, Bank Muamalat had to seek new investors to obtain additional funds to improve its performance. Based on the results of a study by researchers entitled "Analysis of Bank Muamalat Performance and Financial Distress," the researchers found that Bank Muamalat's capital structure was dominated by debt. The results of the Debt to Equity Ratio (DER) calculation, which compares the debt and capital of Bank Muamalat, show that Bank Muamalat's debt is 10 times the capital, and the comparison of Bank Muamalat's debt and assets shows that Bank Muamalat's debt is 90% more than its assets. Therefore, the researcher wants to analyze the capital structure of PT Bank Muamalat and the operational added value of Bank Muamalat. The results of the study indicate that the largest composition of Bank Muamalat's debt is to third parties, namely funds in the form of savings and current accounts. Based on the added value analysis, Bank Muamalat's activities can provide added value to investors, where the results of the EVA calculation from 2018 to 2023 show a positive figure.